Asuhan Keperawatan Pada Ny. N Dengan Penyakit Paru Obstruktif Kronik (Ppok) Di Ruang Paru Rsud Prof. H. M. Yamin,Sh Pariaman - Sakinah Tunnafsih; Linda Marni; Aulia Asman; Kheniva Diah Anggita (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
COPD is a condition characterized by narrowing of the airways. Based on World Health Organization data (2024), Chronic Obstructive Pulmonary Disease (COPD) is the third leading cause of death globally, with mortality rates reaching 3.5 million. The Indonesian Ministry of Health (2023) states that COPD is a significant health issue in Indonesia with a prevalence of 16 million sufferers, while West Sumatra recorded 4,284 cases (West Sumatra Health Office, 2024). Medical record data at Prof. Dr. H. Muhammad Yamin, S.H. Pariaman Regional Hospital shows that the number of COPD patients in 2026 was recorded at 122 patients. The objective of this case study is to describe the application of nursing care for patients with COPD in the Pulmonary Ward of Prof. Dr. H. Muhammad Yamin Hospital, Pariaman. The method used is a case study conducted from February 6th to 10th, 2026, at the Pulmonary Ward of Prof. Dr. H. Muhammad Yamin, S.H. Pariaman Hospital on one subject, Mrs. N, with COPD. The results identified five nursing diagnoses: ineffective airway clearance, impaired gas exchange, ineffective breathing patterns, disturbed sleep patterns, and activity intolerance. Interventions included effective cough training, respiratory monitoring, airway management, sleep support, and activity management. Evaluation over five days showed that all nursing problems—ineffective airway clearance, impaired gas exchange, ineffective breathing patterns, disturbed sleep patterns, and activity intolerance—were resolved. It is expected that the patient will increase awareness in avoiding triggers of breathlessness and maintaining a healthy lifestyle to prevent recurrent exacerbations.